Crab biodiversity under different management schemes of mangrove ecosystems - M. Bandibas; V. Hilomen (Global Journal of Environmental Science and Management, 2016)
Reforestation is one of the Philippines’ government efforts to restore and rehabilitate degraded mangrove ecosystems. Although there is recovery of the ecosystem in terms of vegetation, the recovery of closely-linked faunal species in terms of community structure is still understudied. This research investigates the community structure of mangrove crabs under two different management schemes: protected mangroves and reforested mangroves. The transect-plot method was employed in each management scheme to quantify the vegetation, crab assemblages and environmental variables. Community composition of crabs and mangrove trees were compared between protected and reforested mangroves using non-metric multi-dimensional scaling and analysis of similarity in PRIMER 6. Chi-squared was used to test the variance of sex ration of the crabs. Canonical Correspondence Analysis was used to determine the relationship between crabs and environmental parameters. A total of twelve species of crabs belonging to six families were identified in protected mangroves while only four species were documented in reforested mangroves. Perisesarma indiarum and Baptozius vinosus were the most dominant species in protected and reforested mangrove, respectively.  Univariate analysis of variance of crab assemblage data revealed significant differences in crab composition and abundance between protected mangroves and from reforested mangroves (P